Membrane computing : 19th International Conference, CMC 2018, Dresden, Germany, September 4-7, 2018, Revised selected papers /: 19th International Conference, CMC 2018, Dresden, Germany, September 4-7, 2018, Revised selected papers. (2019) - Unknown
No abstract available